2023
DOI: 10.1039/d2nj05750f
|View full text |Cite
|
Sign up to set email alerts
|

A near-infrared fluorescent probe for detection of H2S and its application in monitoring meat freshness and plant growth under aluminium-induced stress

Abstract: Hydrogen sulfide (H2S) has attracted increasing attentions due to its multiple roles not only as the unpleasant gas released by spoiled food and toxic substance in industrial waste, but also...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In addition, 340 was used to image exogenous H 2 S in mice. Zeng and Wu reported similar probe 341 (CHO-OH-NO 2 ), which incorporates an ortho -aldehyde for increased selectivity and a short polyethylene glycol motif for enhanced solubility . This probe provided a turn-on response to H 2 S at 718 nm and good selectivity for H 2 S over competing analytes.…”
Section: Electrophilic H2s Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 340 was used to image exogenous H 2 S in mice. Zeng and Wu reported similar probe 341 (CHO-OH-NO 2 ), which incorporates an ortho -aldehyde for increased selectivity and a short polyethylene glycol motif for enhanced solubility . This probe provided a turn-on response to H 2 S at 718 nm and good selectivity for H 2 S over competing analytes.…”
Section: Electrophilic H2s Probesmentioning
confidence: 99%
“…Zeng and Wu reported similar probe 341 (CHO-OH-NO 2 ), which incorporates an ortho-aldehyde for increased selectivity and a short polyethylene glycol motif for enhanced solubility. 372 This probe provided a turn-on response to H 2 S at 718 nm and good selectivity for H 2 S over competing analytes. Further applications included developing paper test strips for H 2 S 375 Careful selectivity studies in 50% MeCN in buffer showed some probe activation by 1 mM Cys, but less for GSH, and partial probe deactivation by SO 3 2− .…”
Section: Electrophilic H 2 S Probesmentioning
confidence: 99%
“…Recent investigations on fluorescent probes for H 2 S detection are listed in Table S1 † for comparison. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Although many probes have been reported to show high sensitivity and selectivity, the measurement span (linear range) values were relatively narrow and limited the practical applications. Herein, the optical capabilities of the probe TPABF-HS were tested, and the linear range was especially focussed on.…”
Section: Optical Capabilities Of the Detection Systemmentioning
confidence: 99%
“…[22][23][24] The reported recognition mechanisms involve azide reduction, copper precipitation and nucleophilic attack on ethers, esters and double bonds, while the selected fluorophores include coumarin, rhodamine, naphthalimide and hemicyanine. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] For evaluating the practical application of fluorescent probes, the key performance indicators include selectivity (anti-interference), sensitivity (limit of detection (LOD)) and measurement span (linear range).…”
Section: Introductionmentioning
confidence: 99%